Severidad y comorbilidades de los casos de dengue en adultos con diabetes mellitus del Hospital Regional de Loreto, en los años 2018 al 2023 - Mamani Mamani, Jose Luis (2025)
GENERAL OBJECTIVE: To evaluate the severity and comorbidities of Dengue cases in adults with Diabetes mellitus at the Regional Hospital of Loreto 2023. MATERIALS AND METHODS: A quantitative study of 150 cases and 150 controls will be carried out in order to compare cases of Dengue with type 2 DM and cases of Dengue without type 2 DM. Analytical since it will allow the inference of the results looking for an association between both groups. Not paired that represents the cases as they are presented in the infectology service of the Regional Hospital of Loreto. The hypothesis will be contrasted by means of 95% confidence logistic regression with the statistical package SPSS v 25. CONCLUSIONS: The transposition of infectious and chronic diseases at the local level requires sharpening the local evidence in order to achieve an adequate management at the hospital level of the patient with Dengue and Type 2 Diabetes Mellitus in order to contribute to the reduction of mortality and severe cases.